Ne-ne in Hawaii--Preliminary report on the Ne-ne in Hawaii - Elder, William H (Wildfowl, 1957)
Just eight years ago the world's population of the ne-ne had reached an all-time low. But thirteen birds remained in all the aviaries of the world--all in the Hawaiian Islands. Except two lone birds, all were in the flock of Herbert C. Shipman, long their protector. Little was known of their status in the wild. That they were scarce, all agreed. In the five years since Paul Baldwin's (1945) study, Ne-ne had been seen less than half a dozen times. The Schwartzes (1949) had failed to find any birds in the wild during their two years of intensive field work in the islands. Smith (1952) estimated their numbers in the wild as less than 30.